2004
DOI: 10.1021/jp037187b
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Dispersive XAFS Studies on the Spontaneous Dispersion of PdO and the Formation of Stable Pd Clusters in Zeolites

Abstract: Spontaneous dispersion and clustering processes of Pd were measured by means of the energy-dispersive EXAFS method. The spontaneous dispersion of bulky metal Pd into highly dispersed PdO was directly observed on the H-type zeolite in the atmosphere of O2. In contrast to H-type zeolites, simple oxidation of the agglomerated Pd was observed on Na-ZSM-5. The structural change of Pd was followed in the atmosphere of hydrogen. The clustering processes of metal Pd depended on the kind of zeolite, and these were cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
49
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 22 publications
4
49
1
Order By: Relevance
“…In the case of Pd-H-ZSM the EXAFS studies showed that during calcinations the dispersion of PdO was dependent on the concentration of Brønsted acid sites [31]. The ratio of Pd/ PdO was also stated to depend on the concentration of the BAS in the zeolite [14][15][16][17][18][19][20]. During the reduction, however, the larger Pd particles ([3 nm) were formed and they migrated to the outer surface of the zeolite [31].…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…In the case of Pd-H-ZSM the EXAFS studies showed that during calcinations the dispersion of PdO was dependent on the concentration of Brønsted acid sites [31]. The ratio of Pd/ PdO was also stated to depend on the concentration of the BAS in the zeolite [14][15][16][17][18][19][20]. During the reduction, however, the larger Pd particles ([3 nm) were formed and they migrated to the outer surface of the zeolite [31].…”
Section: Introductionmentioning
confidence: 96%
“…ions in Pd/Mordenite reduced at 150°C [7]. The ratio Pd/PdO was proposed to depend on the concentration of the BAS in the zeolite [14,20]. In the case of Pd/La 2 O 3, interactions between the metal particles and support have been detected [21].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Zeolites are promising supports for metals because the presence of strongly acidic sites in these materials promotes high dispersion of metal particles. In fact, metal clusters of Pd and Pt with high dispersion were obtained on zeolites having Brønsted acid sites [14,15]. Ultrastable Y (USY) zeolites contain strongly acid sites [16] (ca.…”
Section: Introductionmentioning
confidence: 99%
“…This value is significantly higher than the Ni-O distances (from 1.87 to 2.05 Å ) determined for dehydrated samples by EXAFS (Extended X-ray Absorption Fine Structure) [5][6][7], the number of nearest oxygen neighbours being furthermore lower (between 3 and 4). These discrepancies prompted us to analyse precisely the evolution upon rehydration of the coordination shell around Ni 2+ in a NiNaX sample and this was made possible owing to the recent development of dispersive-EXAFS for the in situ study of catalytic materials, allowing the recording of complete absorption spectra in very short times [8,9].…”
Section: Introductionmentioning
confidence: 99%